A global case meta-analysis of three-dimensional speckle tracking for evaluating the cardiotoxicity of anthracycline chemotherapy in breast cancer - Zhang, Li; Zhang, Rui; Shuai, Ping; Chen, Jie; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Anthracycline cardiotoxicity has become one of the common complications of anthracycline therapy.Regular follow-up of chemotherapy patients with myocardial deformation parameters is helpful for early diagnosis of myocardial damage and protective intervention.This study aimed to investigate the value of three-dimensional speckle tracking imaging (3D-STI) in diagnosing and predicting potential cardiotoxicity in breast cancer patients undergoing anthracycline therapy through meta-analysis based on global cases collection. Methods: Relevant case-control studies published prior to November 2021 were extracted to assess cardiotoxicity by 3D-STI in breast cancer patients undergoing chemotherapy. Weighted mean difference (WMD) and 95% confidence interval (CI) were used as pooled statistics. Meta regression and subgroup analysis were employed to identify sources of heterogeneity and publication bias was evaluated by Egger test and funnel plot. Results: A total of 1515 breast cancer patients from 14 studies were enrolled and followed up for 4 or 6 cycles of chemotherapy. Following chemotherapy, absolute values of Left ventricular ejection fraction (LVEF) WMD=-1.59, 95%CI (-1.99, -1.20); p＜0.001; global longitudinal strain (GLS) WMD=2.19, 95%CI (1.87, 2.51); p＜0.001;global circumferential strain (GCS) WMD =1.69, 95%CI(1.11, 2.26); p＜0.001;global radial strain (GRS) WMD=-1.72,95%CI(-2.44,-1.00); p＜0.001 and global area strain (GAS) WMD=6.25, 95%CI( 4.48, 8.02); p<0.001 were decreased. A medium degree of heterogeneity was shown for values of LVEF (I2=44.4%, p=0.037) while values for GLS (I2=59.0%, p=0.003), GCS (I2=81.3%, p<0.001) and GRS (I2=57.5%, P=0.004) showed a large degree of heterogeneity. Egger test and funnel plot showed no significant publication bias in GLS, GCS and GAS data(all p＞0.05). Conclusions: 3D-STI has utility for the non-invasive and objective evaluation of changes in left ventricular function in breast cancer patients undergoing chemotherapy with anthracyclines.The current findings have clinical potential for the early evaluation of myocardial injury caused by chemotherapy toxicity.